2015
DOI: 10.1002/14651858.cd004402.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Steroids for symptom control in infectious mononucleosis

Abstract: There is insufficient evidence to the efficacy of steroids for symptom control in infectious mononucleosis. There is a lack of research on the side effects and long-term complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
0
33
0
3
Order By: Relevance
“…A 2015 Cochrane review found insufficient evidence that steroids improve symptoms in infectious mononucleosis, while it was inconclusive as to whether they increase the risk of complications such as peritonsillar cellulitis and PTA. 16 In the absence of clear benefit and given the possibility of adverse effects, they are therefore not recommended for routine use. 17 This is separate from the issue of steroid use after PTA development, such as intravenous dexamethasone administration in hospitalised patients.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 Cochrane review found insufficient evidence that steroids improve symptoms in infectious mononucleosis, while it was inconclusive as to whether they increase the risk of complications such as peritonsillar cellulitis and PTA. 16 In the absence of clear benefit and given the possibility of adverse effects, they are therefore not recommended for routine use. 17 This is separate from the issue of steroid use after PTA development, such as intravenous dexamethasone administration in hospitalised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids may have analgesic/anti‐inflammatory effects 6 . They have demonstrated efficacy in other inflammatory conditions such as viral croup and glandular fever 7,8 . The publication of a recent large, rigorous trial of corticosteroids for sore throat 9 prompted the updated meta‐analysis discussed here 10 …”
Section: Narrativementioning
confidence: 99%
“…Hay que tener especial cuidado con el uso de ácido acetil salicílico ya que al tratarse de una enfermedad vírica es posible el riesgo de síndrome de Reye. (Rezk et al 2015)…”
Section: Tratamientounclassified